The road dog [videorecording (DVD)] - Glienna, Greg; Boswell, Tony; Stanhope, Doug; Haje, Khrysytne; Fitzsimmons, Greg; Kazurinsky, Tim (Freestyle Digital Media, 2023)
Jimmy Quinn, an alcoholic comedian, travels the country by bus, as the world of standup comedy slowly dies. One day at a motel, his long-lost son David, who has dropped out of med school to be a comedian, appears. They grow closer during their road trip, but tensions rise due to Jimmy's destructive behavior. David learns about Jimmy's failed relationship with Laura and his past as a comedian. Jimmy confronts his unresponsive father in a nursing home and afterwards, Jimmy apologizes to David for his absence. Jimmy's health deteriorates, and David realizes he needs to stop drinking to survive. Thanks to David's actions, Jimmy reconciles with Laura, who has been sober for years. Jimmy decides to stop drinking but at his first sober show, he bombs. He realizes he needs to be drunk to be funny. Due to Jimmy's call to an old friend who books a major TV show, David makes his debut on TV. Proudly watching, Jimmy, who is in bad shape, prepares to perform his next show.